Product Quality and Customer Satisfaction: A Qualitative Analysis of Dairy Products from Anugrah Farm in Kediri Regency - Prasetya, Irvan Ardiansyah; Meilina, Restin (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : This study aims to analyze customer perceptions of the product quality of Anugrah Farm’s milk in Kediri Regency, identify factors influencing customer satisfaction, and provide strategic recommendations to enhance product competitiveness. Design/Methode/Approach : The research employs a qualitative approach, with six informants selected from Anugrah Farm’s customers. Data analysis is conducted using source triangulation techniques through in-depth interviews, observations, and documentation.   Research Finding : The findings reveal that Anugrah Farm’s milk possesses good taste, texture, and freshness quality. However, product packaging is considered less appealing, and a lack of innovation in flavor variety poses a challenge. Affordable pricing and good service are identified as strengths, but promotional strategies need to be strengthened through social media channels.      Theoretical contribution/Originality : This research contributes to the literature on the relationship between product quality and customer satisfaction, particularly for local producers, emphasizing packaging, product variation, and promotional strategies as critical elements for enhancing competitiveness. Practitionel/Policy implication :  Recommendations include innovating packaging designs, diversifying product flavors, improving delivery systems, and strengthening social media promotions to expand market reach and boost customer loyalty..                                              Research limitation : The study is limited to customer perceptions in Kediri Regency.